Pattern Of Fast Food Consumption Among Medical Students And Its Association With Obesity - Sara Usman, Jaweria Yasmin, Maryan Mahad, Faiza Aslam, Sara Usman, Jaweria Yasmin, Maryan Mahad, Faiza Aslam (Students' Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Fast food consumption has been linked to obesity as it contains high saturated fatty acids, sugar, salt, and calories. We conducted this study to determine the pattern of fast food consumption amongst medical students and to assess the association of fast food consumption with obesity. Methods: This cross-sectional study was conducted at Rawalpindi Medical University from February to March 2017. 250 medical students were selected through stratified random sampling technique. A structured questionnaire was used to collect data regarding student’s gender, socio-demographic profile, fast food eating practices, and body mass index (BMI). Data was analyzed using SPSS version 21. Results: There were 150 (60%) female and 100 (40%) male students. Mean age of participants was 20.63±1.69 years and mean BMI was 22.14±3.70 Kg/m2 . 218 (87.2%) students consumed fast food products almost daily to at least once a week on an average, 32 (12.8%) students consumed fast food rarely. Most commonly eaten fast food items were French fries (31%), Pizza and burgers (23% and 15% respectively). 64.8% of fast food consumers had normal weight, 2.0% were obese while, 17.2% and 16.0% fell into categories of overweight and underweight respectively. There was no association between obesity and being overweight with fast food consumption (p-value=0.94). Conclusion: High proportions of medical students consume fast food items, however there is no statistically significant association between fast food consumption and obesity. Key Words: BMI, Obesity, Fast Foods, Medical students, Overweight.